1982
DOI: 10.1128/jcm.16.6.1123-1126.1982
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of age-dependent capsular material on Pasteurella haemolytica serotype 1

Abstract: Extracellular capsular material was demonstrated on early log-phase cells of Pasteurella haemolytica serotype 1 by the fluorescent-antibody and several capsular staining techniques. The presence of this material was shown to be age dependent. Wide capsules were demonstrable on cells from 2to 12-h cultures, whereas cells from 16to 22-h cultures had very little cell-associated capsular material. The Maneval technique most clearly demonstrated the presence of capsules on cells from young (6-h) cultures when compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…The finding that early log-phase P. haemolytica A2 (6 h) cultures possessed larger amounts of capsule than organisms from 18 or 24 h cultures is in agreement with the observations on the A1 serotype [27].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The finding that early log-phase P. haemolytica A2 (6 h) cultures possessed larger amounts of capsule than organisms from 18 or 24 h cultures is in agreement with the observations on the A1 serotype [27].…”
Section: Discussionsupporting
confidence: 89%
“…The production of a capsule in S. aureus was associated with avoidance of opsonophagocytosis through the prevention of opsonin phagocyte-receptor interaction [26]. Early log-phase cultures of P. haemolytica A1 have been shown to produce more capsule than late log-phase cultures [27] and it is reported that early log-phase 1'. h~emolytica A1 are less susceptible to opsonophagocytosis than late log-phase cultures [28].…”
Section: Discussionmentioning
confidence: 99%
“…Serotype specificity may be determined by the many different components of the cell surface of the bacteria. The cell surface of P. haemolytica has been postulated to consist of a polysaccharide capsular material (1,5); however, other macromolecules such as lipopolysaccharides or proteins may also be present (8,16). Since the antiserum used in the initial screening experiment was raised against serotype 1 soluble antigens, it is probable that soluble antigens may also be involved in determining serotype specificity for this bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…At regular intervals, a colony from each type of medium was also suspended in phosphatebuffered saline (PBS; pH 7.2) and was used to inoculate four plates of the same medium for confluent growth. After 6 h of incubation, the growth from one plate was suspended in a small amount of distilled H20 and stained to determine degree of encapsulation by the Maneval technique as described previously (10). The remaining three plates were incubated for 18 h, after which the growth was removed with a cotton swab and suspended in 3 ml of BHI broth containing 15% glycerol (Sigma Chemical Co., St. Louis, Mo.).…”
Section: Methodsmentioning
confidence: 99%
“…The bacterium elaborates a polysaccharide capsule (6,8). The presence of the capsule has been demonstrated to be age dependent (10) and has been suggested as a possible virulence factor of the organism (24). Another attribute ascribed to the bacterium as a potential virulence factor is its ability to produce a leukotoxin which is toxic for bovine pulmonary alveolar macrophages (3,18) and peripheral blood leukocytes (4,16).…”
mentioning
confidence: 99%